Ratio Decidendi of Judges’ Decisions on The Use of Foreign Language Agreements in Indonesia - Amin Amirudin; Dwi Fidhayanti (Journal of Judicial Review, 2025)
This research examines the legal issues surrounding agreements made in foreign languages without an accompanying Indonesian version, specifically regarding the judges’ legal considerations in canceling such agreements and the resulting legal consequences. The study uses a normative juridical method with statutory and case approaches. Primary legal materials were derived from relevant laws and judicial decisions, while secondary materials were obtained from literature studies, analyzed using grammatical interpretation. The study reveals inconsistencies in judicial interpretation. In Decision No. 3395 K/Pdt/2019, the court ruled that an agreement not using Indonesian was null and void. Conversely, in Decision No. 1124 K/Pdt/2020, the court considered a similar agreement valid and binding, despite the absence of an Indonesian translation. This discrepancy reflects a lack of uniformity in upholding the mandatory use of Indonesian as regulated by Article 43(1) of Law No. 2 of 2014 on Notary Position. The article mandates that deeds involving foreign parties must be in Indonesian or accompanied by an Indonesian translation. Violations of this requirement constitute breaches of imperative legal norms, rendering the agreement void. The research aims to promote legal awareness on the mandatory use of Indonesian in agreements and to highlight the need for consistent judicial interpretation to uphold legal certainty.